Serviços clínicos farmacêuticos em unidades do programa Farmácia Popular do Brasil do estado de Sergipe: implantação, implementação e consolidação - Brito, Giselle de Carvalho (2015)
Objective: To establishing, implement and consolidate clinical pharmacy services in units of Farmácia Popular do Brasil program in state of Sergipe. Methods: Initially, systematic review was performed in the databases PubMed, Scopus, EMBASE using the key words "community pharmacy services", "quality assurance health care", "outcome assessment". A longitudinal study of three units of the Farmácia Popular do Brasil in the state of Sergipe on the establishment was carried out (2012), implementation (2013) and consolidation of clinical pharmacy services (2014). The structure of pharmacies was evaluated for physical structure, through the RDC 44/2009, and human resources, the technique of simulated patient. Then three focus groups were conducted (2012, 2013 and 2014) for the perceptions of pharmacists. Finally, we used the coaching technique for establishment, implementation and consolidation of services: dispensing, measurement of blood pressure and blood capillary glucose, medication review and medication therapy management. Results: In the systematic review 42 articles met the inclusion criteria. It was observed that the most valued results were glycosylated hemoglobin (clinical), quality of life (humanistic) and analysis of the cost-effectiveness of the service relationship (economic). In assessing the structure, interventions enabled improvements on all items that were considered non-compliant. However, the overall impression of the pharmaceutical skills for clinical services was considered regular (3) on a scale from 1 to 5. Regarding the focus groups, pharmacists reported expectations in technical support to develop skills, gain knowledge and have a constant monitoring of the researchers, also identified 13 types of barriers. Finally, was designed 520 hours of coaching in place to implement flows and processes, development of standard operating procedures and preparation of strategic plans. In the education training, pharmacists underwent 176 hours of theoretical and practical training and employees to 24h. After the coaching interventions the numbers of services were expanded: there was 767 dispensations in 2012, 1444 in 2013 and 2537 in 2014; 714 measurements of blood pressure and blood capillary glucose in 2012, 2375 in 2013 and 5039 to 2014; 49 consultations of medication review in 2012, 87 in 2013 and 355 in 2014; 15 consultations of medication therapy management in 2012, 33 in 2013 and 271 in 2014. Conclusion: From the good situational diagnosis, the coaching can be considered a technique that assists in establishment, implementation and consolidation of clinical pharmacy services. Combined with a professional training, it allows the individual follow-up in steps as: definition of services and processes, selection of indicators for the assessment and development of strategic plans. In this perspective, this results may support the construction of a differentiated and replicable model of clinical services in community pharmacies.